IPTEKS PERATURAN PERPAJAKAN, KUALITAS PELAYANAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PADA BADAN PENGELOLAH PAJAK DAN RETRIBUSI DAERAH PROVINSI SULAWESI UTARA - Basri, Harianti H.; Pangerapan, Sonny (Universitas Sam Ratulangi, 2018)
Taxes are main source state revenues where state activities such as national development financed from taxes are implement the. This study aims know application knowledge, technology about tax regulations, service quality, and tax sanctions to taxpayers, service quality has a positive effect, Compliance with taxpayers in paying greatly determines effectiveness Motor Vehicle Tax collection, regulations, service quality sanctions influence motor vehicle taxpayer registered in Badan Pengelolah Pajak dan Retribusi Daerah Provinsi Sulawesi Utara.Keywords : Vehicle tax, Tax sanctions, Service Quality and Tax Compliance